Unpacking Teacher’s Self-understanding in Technology Use during COVID-19 Pandemic - Fatimah Zahro Assidiq; Dewi Rochsantiningsih; Nur Arifah Drajati (Randwick International of Education and Linguistics Science Journal, 2021)
The spread of Covid-19 virus has suddenly forced face-to-face learning into online learning. These sudden changes give impacts to professional teaching and learning practices of teacher, teacher not only gives the material but also use technology maximally during this pandemic. The role of teachers and their professional self-understanding has become increasingly complex. This current study led to know about the teacher’s self-understanding in the use of technology during the pandemic. Based on the purpose of the study, this study adopted a small-scale case study with one participant who is an EFL teacher from one of private senior high school in Surakarta, Indonesia. This case study used semi-structure interviews and classroom observations for collecting data techniques. To collect the data, researcher used teacher’s self-understanding theory from Kelchtermans (1993). These teacher’s self-understanding has five components, (1) self-image; (2) self-esteem; (3) task-perception; (4) job motivation; and (5) future perspective. After collecting the data, researcher applied an interactive model analysis. The results showed that (1) teacher’s self-understanding in the use of technology becomes more positive. This understanding brings teacher to become part of booster teaches conducted by The Ministry of Education and Culture, and (2) the inclusion of informal, self-initiated, and self-regulated procedures has supported the modifications of these components of teacher’s self-understanding when she used technology.